Effect of physicochemical parameters on the L-methioninase activity of Methylobacterium sp. and its in vitro anticancer activity in combination with tamoxifen citrate - Kavya Dayanand; Varalakshmi Kilingar Nadumane (SpringerOpen, 2023)
Abstract Background Methionine dependence is a metabolic abnormality observed exclusively in cancer cells. Methionine depletion using methioninase is therefore an attractive strategy for cancer treatment. The current study focuses on the purification of L-Methioninase from a bacterial isolate, Methylobacterium sp. JUBTK33, for its anticancer application in conjunction with Tamoxifen in MCF-7, HepG2, and HeLa cancer cell lines. Results L-methioninase was purified from Methylobacterium sp. JUBTK33 using a DEAE-Sephadex G-200 column, resulting in a 6.15-fold purification with a specific activity of 17.89 U/mg. At 40 °C and pH 8.5, the enzymatic biochemical characteristics demonstrated increased enzyme activity. Na+ ions (1 mM) significantly enhanced the enzyme's activity, while Li+, Mn++, Ni++, Fe++, and K+ had little impact. The highest activity was observed at a 225 µM (2.5%) substrate concentration of methionine, with V max and K m values of 0.48 U/mL/min and 48.23 µM, respectively. The enzyme's potential anticancer effect in combination with TAM was evaluated on HepG2, MCF-7, and HeLa cell lines. It was found to be highly effective on MCF-7 cell lines, with a combination of L-MET-TAM (5 and 10 µg/mL) resulting in 3.72% and 1.0% cell viabilities, and IC50 values of 9.701 µg/mL and 5.72 µg/mL, respectively. On the normal HEK-293 cell line, the combination of L-MET-TAM (10 µg/mL) demonstrated approximately an 18% protective effect compared to TAM alone. Conclusion The combination approach demonstrated remarkable success against cancer cells in vitro, highlighting the need for further investigations to develop it into an effective treatment strategy.